2011
DOI: 10.1111/j.1365-2249.2011.04487.x
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning donor with a combination of tacrolimus and rapamacyn to decrease ischaemia–reperfusion injury in a rat syngenic kidney transplantation model

Abstract: SummaryReperfusion injury remains one of the major problems in transplantation. Repair from ischaemic acute renal failure (ARF) involves stimulation of tubular epithelial cell proliferation. The aim of this exploratory study was to evaluate the effects of preconditioning donor animals with rapamycin and tacrolimus to prevent ischaemia-reperfusion (I/R) injury. Twelve hours before nephrectomy, the donor animals received immunosuppressive drugs. The animals were divided into four groups, as follows: group 1 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 56 publications
0
44
0
1
Order By: Relevance
“…79,80 These immunosuppressants mostly have protective properties on IRI through anti-apoptotic or anti-inflammatory mechanisms. 72,[81][82][83] In addition, tacrolimus also stimulates autophagy in vivo in the brain of mice, 51 while MMF is a potent inducer of chaperonemediated autophagy, a special form of autophagy specific for degradation of oxidized/misfolded proteins mediated by heat shock proteins.…”
Section: Modulation Of Autophagy In Renal Iri With Diuretics and Immumentioning
confidence: 99%
“…79,80 These immunosuppressants mostly have protective properties on IRI through anti-apoptotic or anti-inflammatory mechanisms. 72,[81][82][83] In addition, tacrolimus also stimulates autophagy in vivo in the brain of mice, 51 while MMF is a potent inducer of chaperonemediated autophagy, a special form of autophagy specific for degradation of oxidized/misfolded proteins mediated by heat shock proteins.…”
Section: Modulation Of Autophagy In Renal Iri With Diuretics and Immumentioning
confidence: 99%
“…The role of mTOR in IR‐induced renal injury was evaluated in another set of animals treated with mTOR inhibitor rapamycin, in the presence or absence of clenbuterol, an mTOR activator. The doses of rapamycin and clenbuterol used in the current study were previously reported in the literature to inhibit or activate mTOR, respectively. Rats were randomly divided into five groups as follows (n=5‐7 per group):…”
Section: Methodsmentioning
confidence: 99%
“…Pre‐conditioning of rat donors with calcineurin inhibitors cyclosporine A or tacrolimus decreased structural damage and resulted in improved graft function after kidney transplantation . Moreover, pre‐treatment with tacrolimus combined with rapamycin even improved outcome synergistically . Not all studies could confirm these results, potentially explained by gross differences in experimental set‐up and dosing of immunosuppressives between studies .…”
Section: Donor Pre‐treatmentmentioning
confidence: 99%